2016
DOI: 10.1186/s12909-016-0756-4
|View full text |Cite
|
Sign up to set email alerts
|

Role-playing is an effective instructional strategy for genetic counseling training: an investigation and comparative study

Abstract: Background: Genetic diseases represent a significant public health challenge in China that will need to be addressed by a correspondingly large number of professional genetic counselors. However, neither an official training program for genetic counseling, nor formal board certification, was available in China before 2015. In 2009, a genetic counseling training program based on role-playing was implemented as a pilot study at the Third Military Medical University to train third-year medical students. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
(29 reference statements)
1
18
0
Order By: Relevance
“…Although performance-based assessment is technically challenging, doing so would significantly support the learning outcome and efficacy of role-playing as an active learning method in medical genetics. The authors of this study also noted the amount of effort required to train the teaching faculty; all 20 tutors recruited for the role-playing sessions underwent a significant amount of training and evaluation to become qualified, 44 indicating the importance of a faculty development program in providing authentic and effective learning environments for role-playing sessions.…”
Section: Types Of Active Learning Modalities For Genomic Medicine: Apmentioning
confidence: 86%
See 4 more Smart Citations
“…Although performance-based assessment is technically challenging, doing so would significantly support the learning outcome and efficacy of role-playing as an active learning method in medical genetics. The authors of this study also noted the amount of effort required to train the teaching faculty; all 20 tutors recruited for the role-playing sessions underwent a significant amount of training and evaluation to become qualified, 44 indicating the importance of a faculty development program in providing authentic and effective learning environments for role-playing sessions.…”
Section: Types Of Active Learning Modalities For Genomic Medicine: Apmentioning
confidence: 86%
“…To assess the effectiveness of the role-playing session, students’ attitudes toward the course and the mastery of 42 key genetics concepts in performing genetic counseling were evaluated using self-reported posttraining survey questionnaires (taken by ~300 randomly selected students) and pre- and postsession written examinations (taken by 200 randomly selected students), respectively. 44 The survey results indicated that the program was well received, and ~80% of students agreed that role-playing helped them to 1) understand about genetic counseling; 2) master the knowledge of medical genetics by self-study; and 3) improve their communication skills. 44 These results suggest that, as the University of Alabama study did, role-playing is an effective training method for students to obtain the core competencies of the family history and genomic testing EPAs, which are critical for genetic counseling.…”
Section: Types Of Active Learning Modalities For Genomic Medicine: Apmentioning
confidence: 98%
See 3 more Smart Citations